Tracing the origins of St Helena’s liberated Africans - Xueye Wang; Judy Watson; Helena Bennett; Andrew Pearson; Geoff M. Nowell; Joanne Peterkin; Kate Robson Brown; Alistair Pike; Jason Laffoon; Vicky M. Oelze; Hannes Schroeder (Science, 2026)
In the mid-19th century, St Helena became a key receiving point for Africans “liberated” from illegal slave ships by the British Royal Navy. Of the ~27,000 landed, ~8000 died soon after arrival and were buried locally. In connection with a broader community-led commemorative effort, we analyzed tooth enamel strontium isotope ( 87 Sr/ 86 Sr) data for 152 individuals, including high-resolution intratooth profiles, to identify likely origins and infer forced movements before embarkation. Isoscape-based probabilistic assignment, integrated with historical evidence and published ancient DNA data, constrains homelands ranging from coastal Central Africa to far inland areas, revealing long-distance movements, sometimes beginning in childhood. By refining provenance, these data informed local decisions about care and potential repatriation, highlighting the complexities of return and ultimately supporting reburial on St Helena.